Decisions dealing system of cultural plant type with weighted product method - Hanif, Irfan (Journal of Technology and Computer, 2024)
In the field of agriculture there are some kinds of food crops that are developed and cultivated such as grapes, strawberries, corn, soybeans and so on which are essential food. The farmers should choose the land that is suitable for their food type. If the farmers do not choose the appropriate land, the result is a poor harvest or may be a failure to harvest. However, this is not done, because it takes a long process and impedes the process of cultivation of food crops. However, such problems can be solved using the Decision Support System, because with the Decission Support System (DSS) humans can obtain information in support of decisions. Weighted Product is a decision-support system that is currently evolving with several methods, including the weighted product method. This method is chosen by the authors because the weights product method requires a normalization process, because this method depends on the evaluation of each attribute. The result of the multiplication is not meaningful if not compared (divided) with the standard value. The weight for the benefit attribute serves as a positive rank in the overlapping process, while the cost weight acts as a negative rank. From the results of the research can be concluded among other things: The decision-supporting system built is very helpful in the selection of crop types of food crops UPTD Rare Agriculture.